Structural heterogeneity in populations of the budding yeast Saccharomyces cerevisiae. - Vanoni, M (1983)
Bud scar analysis integrated with mathematical analysis of DNA and protein distributions obtained by flow microfluorometry have been used to analyze the cell cycle of the budding yeast Saccharomyces cerevisiae. In populations of this yeast growing exponentially in batch at 30 degrees C on different carbon and nitrogen sources with duplication times between 75 and 314 min, the budded period is always shorter (approximately 5 to 10 min) than the sum of the S + G2 + M + G1* phases (determined by the Fried analysis of DNA distributions), and parent cells always show a prereplicative unbudded period. The analysis of protein distributions obtained by flow microfluorometry indicates that the protein level per cell required for bud emergence increases at each new generation of parent cells, as observed previously for cell volume. A wide heterogeneity of cell populations derives from this pattern of budding, since older (and less frequent) parent cells have shorter generation times and produce larger (and with shorter cycle times) daughter cells. A possible molecular mechanism for the observed increase with genealogical age of the critical protein level required for bud emergence is discussed.